PERAN GURU DAN ORANG TUA DALAM MENGATASI RENDAHNYA MOTOVASI BELAJAR SISWA DI SD NEGERI SUMBERHARJO - Arizakki Wahyu Gapea; Aulia Putri Zahra; Dhea Pratista Sari; Duta Diva Hayuning Resdika; Devara Bagus Prasetya (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to examine the role of teachers and parents in overcoming low learning motivation among students at SD Negeri Sumberharjo. The research employs a descriptive qualitative approach with the principal and Grade III teachers as subjects and involves all Grade III students. Data were collected through interviews, observations, and documentation. The results indicate that students’ low learning motivation is influenced by the lack of parental support and environmental factors. Teachers play a role in providing motivation and creating engaging learning experiences, while parents contribute by guiding and motivating children to study at home. Collaboration between teachers and parents is essential to enhance students’ learning motivation.